SAT0600 PNEUMOCOCCAL VACCINATION IN PATIENTS WITH AUTOIMMUNE INFLAMMATORY RHEUMATIC DISEASES, TREATED WITH BIOLOGICAL THERAPY AND WITH A LOW LEVEL OF ANTIBODIES - A COHORT STUDY OF PATIENTS WITH VARYING VACCINATION STATUS. (2nd June 2020) - Strandbygaard, L.; Larsen Rasmussen, S.; Fuursted, K.; Hay Kragholm, K.; Leutscher, P. C.; Rasmussen, C.
Abstract : Background: Risk of infection is increased in patients with autoimmune inflammatory rheumatic diseases (AIRD) 1 . Furthermore, disease-modifying antirheumatic drug (DMARD) treatment contributes to this risk 2 . To reduce the risk of serious infections, it is recommended that patients are vaccinated against Streptococcus pneumoniae 3 . However, some AIRD patients do not develop or maintain an adequate antibody response after pneumococcal vaccination 4 . Objectives: The aim of the study was to examine the proportion of patients with low antibody levels, who achieved a protective level of pneumococcal antibodies after vaccination. Methods: Pneumococcal antibodies were measured by a serological assay in patients treated with biologics in a rheumatology outpatient clinic. Vaccination with 23-valent-pneumococcal polysaccarid vaccine was then offered to patients with a protective antibody level below the defined threshold and pneumococcal antibody level was measured at follow-up 2-3 months later. The patients continued their DMARD treatment without any changes. Demographic and clinical data were collected, including age, sex, AIRD diagnosis, duration and activity (high/low), in addition to treatment (biologics, prednisolone, methotrexate) and previous vaccination history. Results: A total of 248 patients with inadequate antibody level accepted vaccination and among those, 137 patients (55%) had previously been vaccinated, 98 patients had not previously been vaccinated and for 13 patients data on vaccination status could not be obtained. At follow-up, 84 patients (34%) achieved a protective level of antibodies. Use of methotrexate as part of the DMARD regimen was associated with an unprotected level of pneumococcal antibodies (Figure 1 ) (p<0, 001). There was no similar association with respect to use of biologics. In the group of patients who had previously been vaccinated, time between vaccinations spanned from 20 to 111 months, median 49 months. There was an association between previous vaccination, and failure in achieving a protective antibody level (Figure 1 ) (p=0, 02), as well as an association between less than 5 years (60 months) between vaccinations and not achieving a protective level. Conclusion: We found that only one-third of patients achieved a protective pneumococcal antibody level after vaccination. Methotrexate treatment was associated with a decreased antibody response, which was not the case for treatment with biologics or prednisolone. Among patients who had previously been vaccinated, significantly less achieved a protective level of antibodies, compared to patients who had not been vaccinated. All 248 patients had a low antibody level at baseline, despite 137 being previously vaccinated. Further studies are warranted to show whether or not a short discontinuation of methotrexate, will better the response to vaccination. References: [1]Wolfe, F. et al. The mortality of rheumatoid arthritis. Arthritis Rheum 1994; 37 (4):481–494. [2]Ramiro, S. et al.). Safety of synthetic and biological DMARDs: a systematic literature review informing the 2016 update of the EULAR recommendations for management of rheumatoid arthritis. Ann Rheum Dis 2017; 76 (6):1101–1136. [3]van Assen S. et al. (). EULAR recommendations for vaccination in adult patients with autoimmune inflammatory rheumatic diseases. Ann Rheum Dis 2011; 70 (3):414–422. [4]Hua, C. et al. Effect of methotrexate, anti-tumor necrosis factor alpha, and rituximab on the immune response to influenza and pneumococcal vaccines in patients with rheumatoid arthritis: a systematic review and meta-analysis. Arthritis Care Res 2014;66 (7):1016–1026. Disclosure of Interests: None declared